School failure and relation with knowledge. Elements of comprehension of the sociological theories (Praxis Educativa, 2016)
In the framework of the investigation related to knowledge (Rapport au savoir) in students of basic education in three different grades (7°, 9° y 10°) in Santiago de Cali, Candelaria and the village of Cabuyal (Colombia), we have found the theories about school failure, in which context emerges the relationship with knowledge in a socialanthropological orientation, which is the referent theory in our research. This theory explains that the phenomenon has been produced just to classify different problems of the school system (basically, those related to students’ poor outcomes). Therefore, the aim of this article is to determine the school failure in its emergency context as well as in its sociological theories. Given the extent of the literature and the geographical areas, our interest is limited to the sociological theories of inequality and the transmission of knowledge in France, important branches of the educational sociology
Keywords: school failure; relationship with knowledge; school; education; sociology of education